گاما رو نصب کن!

{{ number }}
اعلان ها
اعلان جدیدی وجود ندارد!
کاربر جدید

جستجو

پربازدیدها: #{{ tag.title }}

میتونی لایو بذاری!

حاصل عبارت زیر به ازای $y = 2 - x$ و $x = 3$ کدام است؟

$\frac{{xy - 2y + x}}{{3 - ( - x + 2y)}}$

1 ) 

$1$

2 ) 

$\frac{1}{2}$

3 ) 

$\frac{1}{4}$

4 ) 

$ - \frac{1}{2}$

پاسخ تشریحی :
نمایش پاسخ

$\begin{gathered}
  y = 2 - x\xrightarrow{{x = 3}}y = 2 - 3 =  - 1 \Rightarrow \left\{ {\begin{array}{*{20}{c}}
  {x = 3} \\ 
  {y =  - 1} 
\end{array}} \right. \hfill \\
  \frac{{(3)( - 1) - 2( - 1) + x}}{{3 - ( - 3 + 2( - 1))}} = \frac{2}{8} = \frac{1}{4} \hfill \\ 
\end{gathered} $

تحلیل ویدئویی تست

علی مصطفی